The role of forestry sciences in combating climate change and advancing sustainable development goals - Raman, Raghu; Manalil, Sudheesh; Dénes, Dávid Lóránt; Nedungadi, Prema (Frontiers in Forests and Global Change, 2024)
Introduction As ecological disasters loom, forests play a crucial role in mitigating climate change and aligning with the United Nations Sustainable Development Goals (SDGs). This study aims to systematically examine the contribution of forestry science research to the SDGs through a multidisciplinary perspective, highlighting its role in advancing global sustainability efforts. Methods Utilizing the PRISMA protocol, we conducted a comprehensive analysis of 39,841 publications since 2015, focusing on the intersection of forestry sciences with the SDGs. Network and keyword co-occurrence analyses were performed to identify thematic clusters and interdisciplinary linkages among SDGs. Results Our findings indicate a significant focus on SDG 15 (Life on Land) and SDG 13 (Climate Action), emphasizing the forestry sector’s contributions to biodiversity conservation, climate change mitigation, and ecosystem services. The analyses revealed thematic clusters centered around ecological sustainability, sustainable energy, and social development, demonstrating the diverse ways in which forestry research supports the SDGs. Discussion This study highlights the interdisciplinary nature of forestry sciences and identifies key areas of contribution while pointing to potential research gaps. Future research should explore advanced technologies such as AI-driven analytics and remote sensing, socioeconomic impacts of forest-based livelihoods, and innovative reforestation techniques. Strengthening urban forestry, enhancing interdisciplinary cooperation, and improving governance are recommended to ensure continued contributions of forestry sciences to global sustainability and the SDGs.